A A REVIEW LITERATURE EMPLOYEE PERFORMANCE MODEL: MOTIVATION, LEADERSHIP, AND ORGANIZATIONAL CULTURE - Yona Sari, Selvi; lima Krisna, Nandan; Ali, Hapiz (Dinasti Publisher, 2021)
This study aims to determine the model of employee performance that is influenced by motivation, leadership and organizational culture. The method of writing scientific articles is by using qualitative methods and library research or library research. The results of this literature review article are: motivation has a positive and significant effect on employee performance, leadership has a positive and significant effect on employee performance, and organizational culture has a positive and significant effect on employee performance.